Decadal‐scale impacts of changing mangrove extent on hydrodynamics and sediment transport in a quiescent, mesotidal estuary. Issue 5 (22nd January 2022) - Glover, Hannah E.; Stokes, Debra J.; Ogston, Andrea S.; Bryan, Karin R.; Pilditch, Conrad A.
Abstract: Mangroves are often considered integral engineers of morphologic evolution, but mangroves can also opportunistically respond to morphologic change created by abiotic sedimentary processes. Consequently, predicting the response of individual estuarine environments to changes in mangrove extent is challenging. Here, the impact of mangrove extent was explored using in‐situ observations and numerical modeling of the quiescent Waikaraka Estuary in Tauranga Harbor, Aotearoa, New Zealand. Mangrove coverage expanded in the estuary from 1940 until a removal program began in 2005 with the goal of reducing fine sediment and restoring bivalve habitat. In June 2019 water velocity, turbidity, wave height, and bed‐sediment grain size were measured at multiple sites to identify how sediment dynamics in the estuary were responding to removal. Flow in the predominantly sandy lower estuary was ebb dominant, resulting in net sediment export, while flow in the muddy upper estuary was weakly flood dominant, resulting in sediment import and retention. Therefore, fine sediment is unlikely to be flushed out of quiescent estuaries after mangrove removal. A Delft3D numerical model calibrated with in‐situ data showed that tidal asymmetry, velocity skew, and peak ebb‐tide shear stress were not significantly altered by varying the mangrove extent between the 2005 maximum coverage and complete removal. Mangroves did not significantly impact flow in this system; instead, the hydrodynamics and net sediment transport were controlled by tidal interactions with bathymetry. In model runs with mangroves covering all tidal flats, the water velocity on the intertidal flats decreased while the peak ebb‐tide velocity in the main channel increased, indicating that the potential for fine‐sediment export may actually decrease with mangrove removal. These results emphasize the role of mangroves as opportunistic colonizers, not engineers, and highlight the importance of considering site specific parameters when planning mangrove removals. Abstract : Waikaraka Estuary is at dynamic equilibrium, with or without mangroves, and fine sediment is unlikely to leave the estuary. Mangrove expansion has little impact on hydrodynamic processes in infilled or infilling quiescent environments until mangrove reach a maximal extent. Mangrove roots can stabilize sediment and slow change following deforestation.